“Since I went to the conference… I have really thought just how bad lighting fires are”: diversionary conferencing for youth misuse of fire - Pooley, Kamarah (Crime prevention and community safety, 2017)
Youth misuse of fire presents a significant risk to life and property. In Australia, the tertiary prevention of youth misuse of fire involves firefighter participation in diversionary conferencing convened for young people who commit fire-related offences. This approach assumes that young people misuse fire due to a lack of awareness of the consequences, and that education delivered by firefighters in the context of conferencing reduces the risk of future misuse of fire. To explore the validity of this assumption, content analysis of apology letters derived from diversionary conferences convened for young people who committed fire-related offences in New South Wales and Tasmania, Australia, was conducted. Findings suggest that diversionary conferencing with firefighter involvement has the potential to target misuse of fire which manifests from a lack of awareness of the consequences, and that the provision of education has the potential to reduce such misuse of fire by young people.